PENGARUH TINGKAT PENDIDIKAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN PALEMBANG - Suandi, Suandi; Hendriansyah, Hendriansyah; Afriyanti, Afriyanti; Martina, Desi (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2024)
This research aims to find out how much influence the level of education and work motivation has on the performance of Class II Palembang Harbormaster and Port Authority Employees. In this research, the research method used is the explanatory survey research method, which seeks to highlight the relationship between research variables and test the hypotheses that have been prepared previously. The researcher used an explanatory survey method because in this research he tried to find the relationship between the research variables, namely: employee work ability (X1), employee work motivation (X2), and employee performance (Y). Based on the research results, several conclusions were obtained, as follows: 1) The magnitude of the influence of education level on employee performance at the Harbormaster's Office and Palembangn Port Authority is influenced by the dimensions of skills, knowledge and work experience, 2) The magnitude of the influence of motivation on employee performance at the Harbormaster's Office and The Palembang Port Authority is influenced by the dimensions of expectancy, instrumentality (performance-reward link) and valence (attractiveness of rewards).